Hey, Bruce! : an interactive book - Higgins, Ryan T. (Higgins, Ryan T. Mother Bruce (Series), 2022)
Rupert, Thistle, and Nibbs, the three fun-loving mice in Bruce's begrudgingly expansive family, guide readers on a quest for a fun reading experience, with Bruce the ever-reluctant star. As readers turn the page, flip the book, and follow the mice's increasingly silly instructions, Bruce is sent flying and tumbling--all as he looks right up the reader's nose! How will you interact with Bruce?